Management of Catfish Farming in Improving The Economy in The Country is Praising The Economy. South Binjai, Binjai City - Satrio, Bagus; Barus, Elida Elfi (Journal of Management Sains (JMS), 2025)
This activity aims to empower the economy of the residents of Puji Dadi Village by developing catfish cultivation. The method used in this activity is a participatory approach. This activity involves the community as a partner and research subject. This study includes the following steps: socialization, training, mentoring, evaluation, and strengthening. Data was collected through secondary data, direct observations, interviews with key informants, and documents. Data were analyzed using data reduction, presentation, and conclusion-drawing techniques. The study results show that community economic management through the development of catfish cultivation has succeeded in improving the community's knowledge, skills, economic, and social aspects. Factors that affect the success of community management are community support and active participation, stakeholder support and cooperation, availability and feasibility of resources, and the application of participatory methods. The long-term impacts of community management are as follows: the community can develop an independent, sustainable, and competitive catfish farming business, the community is able to improve the quality of life, independence, and welfare; The community can contribute to regional development, especially in the fisheries sector.